Vibration Measurements by Tracking Laser Doppler Vibrometer on Automotive Components - P. Castellini (Shock and Vibration)
This paper describes the application of a Tracking Laser Doppler Vibrometer (TLDV) to the measurement of vibration of some typical automotive component.